Effect of substitution of sugar with stevia (Stevia rebaudiana) powder in squash (Cucurbita maxima) polvoron. - Retiza, Mae Joy Mendoza
The study focused on the utilization of stevia powder in squash polvoron as a healthy alternative substitute to sugar. Three (3) formulations of squash polvoron with the following ratios of stevia powder to the combined weight of all-purpose flour and squash powder: 0.4%, 0.7% and 1% designated as SSI, SS2 and SS3, respectively, were subjected to ranking for preference test and general acceptability test. There was no significant difference among the ranks of the three formulations of the squash polvoron with stevia powder (Kramer?s Rank sum test at α=5). However, in the three trials, SS3 was consistently ranked first and SS1 last. The general acceptability of the SS1, SS2 and SS3 were significantly different (Kruskal-Wallis test at α=5). SS3 had a general acceptability of like moderately while SS1 and SS2 were rated like slightly. Based on this, SS3 was chosen as the best formulation. Squash polvoron with 1% stevia powder was further analyzed to determine its moisture content, pH, aW, and calorie content. Results were compared with the squash polvoron with brown sugar (control). The substitution of brown sugar with stevia powder in squash polvoron significantly changed its physico-chemical properties and calorie content(t-test at α=5). Squash polvoron with 1% stevia powder had a moisture content of 3.52%, pH value of 6.05, aw value of 0.28 and calorie content of 51.78cal/g sample. Squash polvoron with brown sugar (control) had a moisture content of7.51%, pH value of 6.33, aw value of 0.646 and calorie content of 72.18cal/g sample. Squash polvoron with 1% stevia powder formulation was light yellow in color, moderately sweet, had a slightly coarse texture and slight stevia aftertaste. The paired comparison test at α=5 revealed that squash polvoron with 1% stevia powder was significantly preferred over the control. Duo trio test at α=5 revealed that there was a significant difference in the overall sensory attributes of the two products. Stevia powder is a potential sweetener for squash polvoron. Squash polvoron with 1% stevia powder had high acceptability among grade school, high school, college students and adults including senior citizens. Forty two percent (42%) of the respondents rated the product like very much and 33% rated like moderately.